Potato Shoot Tip Cryopreservation. A Review - Kaczmarczyk, Anja; Rokka, V-M.; Keller, J.E.R. (Springer, 2010)
Potato is one of the most important crops worldwide. Genetic resources of potato (Solanum tuberosum L. ssp. tuberosum) and related cultivated species are conserved through storage of tubers, in vitro plants and in cryopreservation. Cryopreservation, storage in or above liquid nitrogen, is the best option to maintain vegetatively propagated plants in the long term. The present review gives comprehensive information about various cryopreservation techniques for potato published from 1977 until the present. It discusses factors that affect the process and success of cryopreservation, such as donor culture conditions, preculture, cooling, warming and post-culture treatments. Studies are presented that analyse the histological and ultrastructural changes after different cryopreservation steps and the morphological pathways during regeneration of plants after rewarming. The maintenance of genetic stability in potato after cryopreservation has also been demonstrated by various phenotypic and molecular methods.The first thermal analyses on potato shoot tips are presented using differential scanning calorimetry to analyse the state of water during cooling and warming. Biochemical analyses of different compounds, such as soluble sugars and proteins, have been performed to understand and improve existing cryogenic methods. Potato is an example where successful virus elimination has been obtained via cryopreservation of shoot tips (cryotherapy). There are already cryopreserved collections of potato shoot tips in Germany, Peru, Czech Republic, South Korea and USA, but additional experiments on fundamental aspects of potato cryopreservation will help to improve understanding of the different cryopreservation methods, start new collections in other countries and also build up existing cryocollections of potato.